Résolution d'une promesse de vente immobilière: nécessité de l'avis de 60 jours - Rousseau-Houle, Thérèse (Les Cahiers de droit, 1977)
This appeal was originally heard by a bench of three judges and, afterwards, considered by a bench of nine in an effort to resolve recent contradictory decisions. It was held that the possessor of an immovable under a promise of sale authorizing the promising vendor to retake possession of the property without compensation or indemnity in the event of failure by the promising purchaser to fulfil his obligations under the deed, is entitled to the sixty-day notice prescribed by articles 1040a and following of the Civil code. In the matter, the creditor, did not serve, as required by articles 1040a and 1040d C.c, the 60 days notice on the possessor with promise of sale. The fact that it would be pointless for the creditor to register the notice against his own property upon which the debtor had yet no registered right of ownership has no bearing, in the Court's opinion, upon the conclusion that the creditor is not obliged to give a 60 day notice to the debtor.